Polar Vortex Disruptions by High Latitude Ocean Warming - Hamouda M. E.; Portal A.; Pasquero C. (Geophysical Research Letters, 2024)
Mid-latitude extreme cold outbreaks are associated with disruptions of the polar vortex, which often happen abruptly in connection to a sudden stratospheric warming. Understanding global warming (particularly Arctic amplification) impacts on forecasting such events is challenging for the scientific community. Here we apply clustering analysis on the Northern Annular Mode to identify surface precursors and the governing mechanisms causing polar vortex disruption events. Two clusters of vortex breakdown emerge; 65% of the events, mainly displacements, are associated with high-latitude Ocean warming in the North Pacific and in Barents-Kara Sea. Such warming may cause large scale modifications of the tropospheric flow that favors a slowdown of the stratospheric vortex. The persistence of Ocean surface temperature patterns favors polar vortex disruptions, potentially improving prediction skills at the sub-seasonal to seasonal time scales.Extreme winter weather is linked to cold arctic outbreaks when the polar air mass spills frigid air to mid-latitudes. This phenomenon often follows weak polar vortex (in extreme cases a Sudden Stratospheric Warming) episodes. Forecasting such events is challenging as many climatic components can be involved. In this study, it is found that 65% of the events start with a certain surface air mass distribution (Low Pressure over the North Pacific, High Pressure over Eurasia). Such distribution is triggered by high latitude ocean warming corresponding to warm temperature anomalies in the North Pacific Ocean and Sea Ice loss in Barents-Kara seas. This result helps predicting the probability of polar vortex disruptions in winter, potentially leading to enhanced sub-seasonal to seasonal cold outbreaks forecast.Around 65% of weak polar vortex (WPV) events are preceded by tropospheric pressure anomalies High-latitude ocean warming explains tropospheric air mass modification, which favors upward wave flux that disrupts the stratosphere Probabilistic forecast of WPV events is possible using an ...